Peningkatan Kosakata Bahasa Arab dengan Menggunakan Game Educandy Siswa Kelas VII - Rusli, Sulfiani; Pamessangi, Andi Arif; Kartini; Anastasyah (South Sulawesi Education Development, 2025)
This study aims to improve Arabic vocabulary among seventh-grade students at Madrasah Tsanawiyah Assalam Salu Induk through the use of Educandy-based educational games. The issue faced is the low mastery of Arabic vocabulary among students, which affects their ability to understand Arabic learning materials as a whole. The Educandy game was chosen because it can create a fun, interactive learning environment that motivates students to be more active in learning. This study uses an experimental method with a pre-test design to measure the improvement in vocabulary mastery before and after using the game. The subjects of the study consisted of 15 seventh-grade students. The results of the study showed a significant improvement in Arabic vocabulary mastery, as measured by the comparison of pre-test and post-test scores. Based on these findings, it can be concluded that the use of the Educandy game can effectively improve students' Arabic vocabulary. This study is expected to contribute to the development of more engaging and effective Arabic learning methods at Madrasah Tsanawiyah Assalam salu induk luwu.